2008
DOI: 10.4314/gjass.v7i1.2364
|View full text |Cite
|
Sign up to set email alerts
|

Seed Varieties And Quantities Of Chemical Fertilizers Used In Agricultural Production In Northern Nigeria

Abstract: Two separate researches were conducted in northern Nigeria. The first study (1996/97) covered Kano, Jigawa and Katsina States and the second (2002/03) covered Kano and Katsina States. These States have high agricultural production potentials and are significant in both biophysical characteristics and population density for the larger part of northern Nigeria. These two researches compared the seed types and quantities of chemical fertilizers used in the two separate agricultural seasons. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
1
1
0
Order By: Relevance
“…However, all the farmers believed that the four thematic areas evaluated in this study were key challenges impeding subsistence farming. This study corroborates Okoruwa et al, (2020) [6] who reported that the problems confronting subsistence agriculture are multi-dimensional and, in fact, numerous.…”
Section: Access To Informationsupporting
confidence: 90%
See 1 more Smart Citation
“…However, all the farmers believed that the four thematic areas evaluated in this study were key challenges impeding subsistence farming. This study corroborates Okoruwa et al, (2020) [6] who reported that the problems confronting subsistence agriculture are multi-dimensional and, in fact, numerous.…”
Section: Access To Informationsupporting
confidence: 90%
“…Agricultural inputs include certifi ed seedlings, pesticides, herbicides, and fertilizers [6]. The unavailability and often time high costs of these inputs hinder the productivity of the subsistence farmers thereby leading to food scarcity and food poisoning.…”
Section: Availability Of Agricultural Inputsmentioning
confidence: 99%